The Mystical Figure of Haji Ahmad Mutamakin from the Village of Cebolek (Java) - Wieringa, Edwin (Studia Islamika, 1998)
History of the Islamization process in rural Javanese society has given birth to a mystic figure named Haji Cebolek Mutamakin of the village; a village in the North Coast region, Pati, Central Java. This figure is estimated to live around the beginning of the 18th century. He is widely known by the public-especially among students through a Java-written book Yasadipura I (1729-1803), a poet Sultan palace Pakubuwana IV, entitled Fiber Cebolek.DOI: 10.15408/sdi.v5i1.759